Os dois lados do espelho: literatura e história na obra de Arthur Bispo do Rosário - Pimentel, Alexandre da Silva (2015)
Arthur Bispo do Rosário (1909-1989) lived for more than fifty years of his life in a mental hospital in Rio de Janeiro. Diagnosed as schizophrenic-paranoid, he said he was a chosen by God, believing and claiming to be a messiah imbued by a divine mission which he dedicated his life to: rebuilding the world to deliver it to God on judgment day. In this process, he "forgets" who he was and forges for himself a new existence which he ends up adopting as identity, destroys his own "ego" and builds himself a new subjectivity, a new mythical biography in its origins and refuses to accept or validate any other version that differs from the truth that he built himself, the truth that would become not only the propeller of his creation, but the reason for his existence. The historical-biographical discourse is a firmly based on narrative historical facts and documentary evidence of the events' truth; there is a primary commitment to truth, to the real and the scientific work that he develops, which gives itself credibility as a historical document. But in this particular case, the biography's subject questions the historical truth which contradicts his assertions, disregards a discourse constructed from facts and official documentary sources and proposes a mythical autobiography about his origins defending it and living it as the only truth. Thus, there is a clash between the historical and biographical and the fictional discourse of Arthur Bispo do Rosário that is considered in this work as a kind of representation (or variation) of literary discourse. This paper will discuss the issue of discursive shock through the analysis of both discourses and a selection from the artist's collection (since these parts are considered as compositional elements of his narrative) and understand what are the impacts of the conflict the particular composition of each of the speeches involved in this specific context, how the nuances and relationships appear between literature and history in this discursive confrontation environment established by the work of Arthur Bispo do Rosário. Keywords: Literature; History; Myth; Madness; Fiction